2014
DOI: 10.1021/co500028h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Monodisperse Oligo(Oxyethylene)-Grafted Polystyrene Resins for Solid-Phase Organic Synthesis

Abstract: In a preliminary investigation by our group, we found that poly(styrene-oxyethylene) graft copolymers (PS-PEG), for example, TentaGel resins, are advantageous for gel-phase (13)C NMR spectroscopy. Because of the solution-like environment provided by the PS-PEG resins, good spectral quality of the attached moiety can be achieved, which is useful for nondestructive on-resin analysis. The general drawbacks of such resins are low loading capacities and the intense signal in the spectra resulting from the PEG linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…54,55 In the same way, in addition to the classical PS-DVB polymeric networks of Merrifield resins, other organic polymers like polyvinyls, polyacrylates, cellulose or PS-DVB copolymerised with other polar monomers or modified with hydrophilic flexible units such as polyglycol chains acting as crosslinking units or linkers have been developed and tested as alternative polymeric supports. [56][57][58][59][60] In the last decade, a whole new range of different porous networks, including crystalline and amorphous structures, have blossomed as suitable alternatives to traditional organic polymers. 61 In some instances, they can combine high surface areas, good physicochemical stability and an increasing degree of functional modularity.…”
Section: The Polymer Matrix As a Design Vectormentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 In the same way, in addition to the classical PS-DVB polymeric networks of Merrifield resins, other organic polymers like polyvinyls, polyacrylates, cellulose or PS-DVB copolymerised with other polar monomers or modified with hydrophilic flexible units such as polyglycol chains acting as crosslinking units or linkers have been developed and tested as alternative polymeric supports. [56][57][58][59][60] In the last decade, a whole new range of different porous networks, including crystalline and amorphous structures, have blossomed as suitable alternatives to traditional organic polymers. 61 In some instances, they can combine high surface areas, good physicochemical stability and an increasing degree of functional modularity.…”
Section: The Polymer Matrix As a Design Vectormentioning
confidence: 99%
“…In this regard, the introduction of long aliphatic or ether spacers favouring compatibility with a wide range of solvents [58][59][60]92,93 or the substitution of DVB by more flexible crosslinkers has been widely explored. 84 Thus, Montanari and coworkers found that the use of long aliphatic spacers (up to 10 methylene units) and low crosslinking degrees (1%) increased the corresponding activities 2-4 times in polymer-supported phase transfer catalysts.…”
Section: Gel-type Polymeric Supportsmentioning
confidence: 99%
“…However, the chemical shifts of C 2 , C 3 and C 5 in β-CD molecule have been overlapped with each other, and thus only one peak appears at 70.79 ppm. This strong peak also covers the methylene group signals in PEG chain (P 2 and P 3 ) at around 70 ppm[36,37]. The peak at 63.63 ppm corresponds to both C 6 in β-CD molecule and the PEG's methylene group that is connected with the end hydroxyl group (P 1 ).…”
mentioning
confidence: 88%
“…Lim et al präsentierten eine effiziente Festphasensynthese einer Bibliothek von Phenyl‐Piperazin‐Triazin‐basierten α‐Helix‐Mimetika (41) 45. Das neuartige monodisperse Oligo(oxyethylen)‐Polystyrolharz (42) zeigt günstige Eigenschaften bei Beladung und Quellbarkeit sowie gleichzeitig optimale Möglichkeiten zur Reaktionsanalytik mit 13C‐Gelphasen‐NMR 46…”
Section: Festphasen‐ Und Flowsyntheseunclassified